Nour Mufied and His Approach in Writing The Al Mufied Dictionary - Hidayat, Surya; Azizah, Azizah; Harson, Iwan; Bahruddin, Uril (Universitas Ahmad Dahlan, 2024)
The Al-Mufied Dictionary is a modern Indonesian-Arabic dictionary widely utilized by learners of Arabic in Indonesia, particularly beginners. This dictionary not only provides vocabulary but also includes example sentences and phrases that learners can apply in context. This study aims to examine the methods employed by Nur Mufid in compiling the Al-Mufied Dictionary and to evaluate its strengths and weaknesses. A qualitative library research method was adopted, with data collected through documentation that explains the dictionary's structure and development methodology. The analysis involved reviewing relevant literature to explore the background and contributions of key figures and dictionaries within this domain. The findings reveal that the dictionary employs a root-based morphological approach and is organized alphabetically in Indonesian. In conclusion, the Al-Mufied Dictionary is highly suitable for Indonesian students due to its alphabetical arrangement in Indonesian and the inclusion of example phrases that facilitate comprehension.